PENGARUH POLITIK HUKUM DAN KETERLIBATAN MASYARAKAT PADA PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Widjaja, Gunawan; Martedjo, Wagiman; Sudrajat, Maman (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The legal political system greatly influences the Indonesian state to become a state based on law, thus requiring the involvement of community components in the process of formulating laws. This is so, because the legal political system will have a vital role in making the law. This is because the direction of the Indonesian state in the application as a state of law uses the concept of Continental European Civil Law, where written law is a very important part of the formation process, and is used as the basis for the implementation of governance. In order to ensure the implementation of legal protection for all people, as well as justice in treatment, and guarantee protection of citizens' rights, it is necessary to establish concrete guidelines in planning and drafting laws. This is intended to be the basis for regulating the process of law-making, starting from the beginning until the time when the law is enacted or applied in regulating the life of the state society. Thus, by creating concrete guidelines and guidelines, each law-making process can be carried out in a definite, consistent, and standardised manner.